SPOTTER: Assessing supply disruption impacts along the supply chain within Life Cycle Sustainability Assessment - Marcus Berr; Didier Beloin-Saint-Pierre; Roland Hischier; Alessandra Hool; Patrick Wäger (Cleaner Logistics and Supply Chain)
The present article introduces the SPOTTER approach, a novel way to assess supply disruption impacts along the supply chain in the short-term (i.e. the next 5 years) and the medium-term (i.e. in 5 to 15 years) within the Life Cycle Sustainability Assessment framework. This approach allows finding the more important supply risks within global supply chains and over different time horizons, which leads to fine-tuned insights that can help creating resilient supply networks. To this end, the SPOTTER approach assesses overall supply disruption impacts for complete supply chains and supply disruption hotspots separately in the short- and medium-term. The overall impacts and hotspots are evaluated from global and country-specific supply disruption events and aggregated into the two categories of 'cost variability' and 'limited availability'. Scores of these impacts and hotspots are calculated by multiplying resource, material and product flows with respective characterization factors, which are case-specific and are defined by diverse indicators of supply disruption probability and vulnerability. The article provides an overview of the SPOTTER approach and its rationale by explaining the selection and use of indicators to define characterization factors and by describing the procedure to calculate the overall impact and hotspot scores. Furthermore, it presents an implementation procedure for the practical application of the approach. Finally, it highlights the data availability and methodological issues that currently affect the implementation practicability and the representativeness of the SPOTTER approach to describe global supply risks in detail and refers to the need for future research and development on this topic.